In adults with multimorbidity, does the provision of social care services have an effect on the use of primary care and secondary care health services? IJPDS (2017) Issue 1, Vol 1:117, Proceedings of the IPDLN Conference (August 2016) - Henderson, David (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Health and social care is an area of high policy importance in the UK. Integration of health boards with local authority provided social care in Scotland in 2016 is a major structural change in delivery of care. Improvements in service and efficiency are expected and indeed required in an era of declining budgets. Intuitively, health and social care are closely linked, particularly for those with multiple morbidities. However, little is known about the relationship between health and social care services and how usage of one has an impact on the other in terms of outcomes and costs. The study aims to describe the methods that have been used to analyse the relationship between social care, primary care and secondary care services. Findings will inform the analysis of a large linked dataset of health care, social care and benefits data that will investigate the interactions between health and social care, multimorbidity and socioeconomic status. Approach A Scoping review of literature aiming to identify academic studies that have made an assessment of the relationship between health care and social care. A search of academic databases will be augmented by a search of grey literature aiming to identify the extent, range and nature of studies. Data will be extracted on populations, study designs, results and recommendations. Results will be visualised in charts alongside a descriptive qualitative synthesis. Results Expected June 2016